ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEDAPATAN RUMAH TANGA MASYARAKAT SEKITAR OBJEK WISATA TAMAN WISATA ALAM (TWA) BATUPUTIH - Berkatrina , Masala; Jolanda Kitsia Juliana Kalangi; Nansi Magret Santa (AGRI-SOSIOEKONOMI, 2021)
This study aims to analyze the influence of factors such as working time, number of family members, wages, education level, mastery of special skills, and age on household income of the community around Batuputih tourist attraction. The data used in this study are primary data and secondary data. The sampling method used is purposive sampling. The method of determining the number of respondents as a sample uses the total quota sampling method. The location selection was based on the consideration that the location is the only natural tourist attraction in Batuputih Bawah Village, Ranowulu District, Bitung City. Analysis of the data used is a multiple linear regression equation model. The results showed that the factors that affect the income of the community around the Batuputih natural tourist attraction are the outpouring of working time, wages and the level of mastery of special skills. Most of the people around the Batuputih natural tourist attraction earn income by working as guides.